Report of a Novel SHOX Missense Variant in a Boy With Short Stature and His Mother With Leri–Weill Dyschondrosteosis - Lucchetti, Laura; Prontera, Paolo; Mencarelli, Amedea; Sallicandro, Ester; Mencarelli, Annalisa; Cofini, Marta; Leonardi, Alberto; Stangoni, Gabriela; Penta, Laura; Esposito, Susanna (Frontiers in Endocrinology, 2018)
Heterozygous mutations in the SHOX gene or in the upstream and downstream enhancer elements are associated with 2-22% of cases of idiopathic short stature (ISS; OMIM#300582) and with 60% of cases of Leri-Weill dyschondrosteosis (LWD; OMIM#127300) with which female subjects are generally more severely affected. Approximately 80-90% of SHOX pathogenic variants are deletions or duplications, and the remaining 10-20% are point mutations that primarily give rise to missense variants. The clinical interpretation of novel variants, particularly missense variants, can be challenging and can remain of uncertain significance. Here, we describe a novel missense variant (c.1044 G>T, p.Arg118Met) in a Moroccan boy with a disproportionately short stature and without any radiological traits or bone deformities and in his mother, who had a disproportionately short stature and a Madelung deformity. This variant has not been reported to date in the updated SHOX allelic variant or Human Gene Mutation Databases nor is it listed as a polymorphism in the ExAC browser, dbSNP, or 1000G. This mutation was predicted to be deleterious by three different bioinformatics tools since it modifies an amino acid in a highly conserved DNA binding domain of the SHOX protein. Based on this evidence, the patient was treated with recombinant human growth hormone (rh-GH).